Novas sinonímias e correções em Simulium com a revalidação de S. pruinosum Lutz, 1904 (Culicomorpha, Simuliidae) Simulium new synonymies and corrections, with resurrection of Simulium pruinosum Lutz, 1904 (Diptera, Culicomorpha, Simuliidae) - Victor Py-Daniel (Universidade de São Paulo, 1989)
Consideram-se Simulium antunesi (Lane & Porto, 1940), S. mauense Nunes de Mello, 1974 e S. nilesi Rambajam, 1979 sinonímias de Simulium perflavum Roubaud, 1906; S. sucamense Nunes de Mello, 1974 e S. santaelenae Ramirez-Pérez & Peterson, 1981 sinonímias de S. (Psilopelmia) iracouboense Floch & Abonnenc, 1946; S. major Lane & Porto, 1940 sinonímia S. (Helmicnetha) rubrithorax Lutz, 1909. Ressalta-se a utilização errônea do nome Grenierella para o subgênero Grenieriella Vargas & Nájera, 1951. Simulium (G.) pruinosum Lutz, 1910 é revalidada, e sugere-se que S. nigrimanum Macquart, 1838 volte a ocupar a posição de species inquirendae. The following synonyms are proposed: Simulium antunesi (Lane & Porto, 1940), Simulium mauense Nunes de Mello, 1974 and Simulium nilesi Rambajam, 1979 are synonyms of Simulium perflavum Roubaud, 1906; Simulium sucamense Nunes de Mello, 1974 and Simulium santaelenae Ramirez-Perez & Peterson, 1981 are synonyms of Simulium (Psilopelmia) iracouboense Floch & Abonnenc, 1946; Simulium major Lane & Porto, 1940 are synonym of Simulium (Hemicnetha) rubrithorax Lutz, 1909. The recent use of the miswriting name Grenierella to the subgenus Grenieriella Vargas & Nájera, 1951 is mentioned. Simulium (Grenieriella) pruinosum Lutz, 1910 is revalidated and Simulium nigrimanum Macquart, 1838 should be considered species inquirendae.